Cryopreservation activities in Belgium - Panis, Bart (2023)
1st Meeting of the ECPGR Cryopreservation Working Group Concept for development of a rational and efficient way to collaboratively conserve under cryopreservation the relevant European plant genetic resources 3-4 May 2023 Crop Research Institute, Prague, Czech Republic